Pengaruh Kepemimpinan Kepala Sekolah terhadap Manajemen Organisasi Paud - Aslah Mutiah; Dermawan Dermawan; Suhailah Abnan; Kasman Kasman (Simpati, 2026)
This study is motivated by the importance of the principal’s leadership role in improving the effectiveness of organizational management in Early Childhood Education (ECE) institutions. As an educational leader, the principal is responsible for organizing, directing, and coordinating all available resources in ECE institutions to ensure they function effectively and efficiently. The aim of this study is to analyze the influence of principal leadership on ECE organizational management. The research method used is a qualitative approach with data collection techniques including observation, interviews, and documentation studies. The findings indicate that effective principal leadership, particularly democratic and participatory leadership styles, has a positive influence on improving the quality of ECE organizational management in terms of planning, organizing, implementation, and program evaluation. In addition, effective leadership also enhances teacher performance and creates a conducive working environment. The implication of this study suggests that improving the leadership competence of principals is essential to support the optimal management of ECE institutions.